Acute performance responses during repeated matches in combat sports: A systematic review - Kons, R. L.; Orssatto, L. B. R.; Detanico, D. (Journal of Science and Medicine in Sport, 2020)
Objective: Investigate the acute effects of repeated combat sports matches on vertical jump and handgrip strength performance in grappling and striking modalities.